2020
DOI: 10.1038/s41598-020-79220-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural network alterations related to serum cortisol levels in drug-naïve, first-episode major depressive disorder patients: a source-based morphometric study

Abstract: Higher cortisol levels due to a hyperactive hypothalamic–pituitary–adrenal axis have been reported in patients with major depressive disorder (MDD). Increased cortisol levels change both the brain morphology and function in MDD patients. The multivariate source-based morphometry (SBM) technique has been applied to investigate neuroanatomical changes in some neuropsychiatric diseases, but not MDD. We aimed to examine the alterations in gray matter (GM) networks and their relationship with serum cortisol levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The subjects in the present study overlapped with those in our published study (Kakeda et al, 2020;Nguyen et al, 2020;Watanabe et al, 2020), however, no study analyzed the amygdala. The study protocol was approved by the Ethics Committee of the University of Occupational and Environmental Health, Japan.…”
Section: Participantsmentioning
confidence: 54%
“…The subjects in the present study overlapped with those in our published study (Kakeda et al, 2020;Nguyen et al, 2020;Watanabe et al, 2020), however, no study analyzed the amygdala. The study protocol was approved by the Ethics Committee of the University of Occupational and Environmental Health, Japan.…”
Section: Participantsmentioning
confidence: 54%
“…In line with the study phase protocol, no exclusion of subjects was made based on the dominant arm. The subjects in the present study overlapped with those in our published studies [ 13 , 21 , 29 ], however, no study has analyzed the correlation between amygdala subregions and blood metabolite levels.…”
Section: Methodsmentioning
confidence: 78%
“…It is speculated that connections from the amygdala to the hypothalamus activate the hypothalamic-pituitary-adrenal (HPA) axis and cortisol response [ 5 ]. In addition, it has been reported that individuals with the s/s genotype show enhanced cortisol secretion in response to acute psychological stressors [ 20 ], which may increase cortisol levels, and may be associated with alterations in the prefrontal network in the early stage of MDD [ 21 ]. Brain-derived neurotrophic factor (BDNF) is a neurotrophin that is vital for the survival, growth, and maintenance of neurons in key brain circuits involved in emotional and cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another research in line with this study revealed that higher levels of anhedonia are positively associated with cortisol reactivity to stress (Cunningham et al, 2021 ). In addition, previous fMRI studies have demonstrated that brain reward circuitry in anhedonia is related to inflammation and cortisol levels in MDD (Felger et al, 2016 ; Harrison et al, 2016 ; Nguyen et al, 2020 ). For example, Felger et al indicated that increased inflammation, especially CRP and IL-6 levels, were associated with reduced functional connections involved in brain reward circuits in MDD (Felger et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we found that serum cortisol levels increased in patients with MDD compared with those in HCs. Higher cortisol levels are considered one of the important features of depression (Vreeburg et al, 2009 ; Nguyen et al, 2020 ). Consistent with previous studies, this study supports that hyperactivation of the HPA axis may be involved in the pathogenesis of MDD.…”
Section: Discussionmentioning
confidence: 99%